2017
DOI: 10.1177/0022167817739714
|View full text |Cite
|
Sign up to set email alerts
|

The Social World of Self-Actualizing People: Reflections by Maslow’s Biographer

Abstract: Maslow’s concept of self-actualization has been a bulwark of humanistic psychology for more than 50 years, and has increasingly gained international appeal beyond its original nexus within the United States. His description of the high achieving characteristics of self-actualizing men and women has influenced theorists and practitioners in such fields as counseling, education, health care, management, and organizational psychology. Through these same decades, Maslow’s formulation has also been criticized as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, to supplement the relatively limited body of explicitly humanistic leadership literature to date (e.g., Beshai, 2012; DuBose, 2020; McWhinney, 1984; Miller et al, 2010; Raskin, 2020; Rego et al, 2008; Saiter, 2009; Schott, 1992), in preparing this article, we intentionally strived to build bridges between existential–humanistic and mainstream psychology by drawing from the latter to provide empirical support for Maslow’s theorizing in the spirit of Bland (2019), Bland and DeRobertis (2020), and Kaufman (2020). In so doing, we have (a) further demonstrated that his ideas on eupsychian leadership “appear to be more realistic than some criticisms regarding their allegedly utopian aims would suggest” (Rego et al, 2008, p. 187) and, therefore, (b) further contributed to an emerging body of literature that serves to clear up misconceptions about Maslow (see also Bland & DeRobertis, 2019, 2020; Compton, 2018; Henry, 2017; Hoffman, 2017) as an antidote to the “recurrent Maslow bashing that one finds in the literature” (Winston et al, 2017, p. 309).…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, to supplement the relatively limited body of explicitly humanistic leadership literature to date (e.g., Beshai, 2012; DuBose, 2020; McWhinney, 1984; Miller et al, 2010; Raskin, 2020; Rego et al, 2008; Saiter, 2009; Schott, 1992), in preparing this article, we intentionally strived to build bridges between existential–humanistic and mainstream psychology by drawing from the latter to provide empirical support for Maslow’s theorizing in the spirit of Bland (2019), Bland and DeRobertis (2020), and Kaufman (2020). In so doing, we have (a) further demonstrated that his ideas on eupsychian leadership “appear to be more realistic than some criticisms regarding their allegedly utopian aims would suggest” (Rego et al, 2008, p. 187) and, therefore, (b) further contributed to an emerging body of literature that serves to clear up misconceptions about Maslow (see also Bland & DeRobertis, 2019, 2020; Compton, 2018; Henry, 2017; Hoffman, 2017) as an antidote to the “recurrent Maslow bashing that one finds in the literature” (Winston et al, 2017, p. 309).…”
Section: Discussionmentioning
confidence: 73%
“…In addition to the above two theoretical foundations, scholars have explained the mechanism of idolatry from the perspectives of self-actualization and relational needs. Self-actualization refers to an individual’s desire to continuously stimulate his or her own potential and realize personal pursuits ( Hoffman, 2020 ). It is a state of mind that is commonly possessed by human beings.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Therefore, selfactualisers make up only a small percentage of people (about 1%) (Clark, 2008). Such people do not share personal characteristics with neurotic personalities and immature people (Hoffman, 2017). They are independent and creative, with a philosophical outlook, democratic in relations, high-performance, etc.…”
Section: Introductionmentioning
confidence: 99%